Alderstyranni og dekronologisering - Heggli, Gry (Tidsskrift for kulturforskning, 2004)
The main purpose of this article is to present and discuss age as an axis of social life. The age-based categories of child(hood), youth and adult(hood) have yet to be explored. Unless one is working with elderly people or the very young, age is unmarked. The topics discussed within this frame all relate to the adult role and its obvious position as the dominant, making adulthood both invisible and powerful in its role as norm. A principal value of adulthood is autonomy; a value which impacts significantly on how we define and practise the upbringing of our children. Another line of argument presented in this article is a discussion of alternative concepts and ways of thinking about age, and the author introduces the thoughts of the British scholar Nick Lee and his way of playing with the dichotomy of becoming versus being.